Gender Patterns in Hypertext Reading - Protopsaltis, Aristidis; Bouki, Vassiliki (Ergonomics Open Journal, 2009)
The effect of gender in learning has often been the focus of research because of its potential implications in academic achievement. However, the effect of gender in hypertext reading has not been thoroughly investigated. The Web in general and the hypertext in particular has modified the way people access and use information. This paper reports the findings of an empirical study into gender differences in hypertext reading. The study focuses on text-based electronic documents. The study is a mixed method design, with the use of the think-aloud protocols and a between subjects experiment. It examines some original variables not previously studied comprehensively, such as coherence of transactions, sum of selected hyperlinks, and hyperlink location. Forty two participants (30 males and 12 females) read a hierarchically structured hypertext and then, all answered the same set of questions. The data consisted of reading times, comprehension scores, reading strategies, coherent links, hyperlink location, sum of hyperlinks, and the sum of read nodes. The results show that gender did not significantly affect any of the measured variables.<br